2016
DOI: 10.1097/phm.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Mobile Health to Promote Self-Management in Spina Bifida

Abstract: Use of the iMHere system in spina bifida is feasible and was associated with short-term self-reported improvements in self-management skill. This system holds promise for use in many diverse chronic care models to support and increase self-management skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 28 publications
0
42
1
Order By: Relevance
“…In light of the growing need of persons with BSA, we developed iMHere (Interactive Mobile Health and Rehabilitation), an mHealth system to support a self-management program [ 19 ]. The initial version of iMHere 1.0 connected adults with disabilities to clinicians and was implemented to support individuals with SB [ 20 ] and spinal cord injury (SCI). iMHere 1.0 was developed on an Android platform and did not support iPhone or other non-Android users.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the growing need of persons with BSA, we developed iMHere (Interactive Mobile Health and Rehabilitation), an mHealth system to support a self-management program [ 19 ]. The initial version of iMHere 1.0 connected adults with disabilities to clinicians and was implemented to support individuals with SB [ 20 ] and spinal cord injury (SCI). iMHere 1.0 was developed on an Android platform and did not support iPhone or other non-Android users.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to apps specifically targeting persons with a DD, Dicianno and colleagues [35][36][37] developed an integrated system to support self-management of several health-related activities among individuals with spina bifida [38], which showed improvements in self-management abilities [35]. The interactive Mobile Health and Rehabilitation (iMHere) system comprises 6 smartphone modules providing reminders to individuals to take their medications, perform their catheterization and bowel management programs, examine their skin, complete a survey assessing depressive symptoms, and send and receive messages to and from the clinician.…”
Section: Medication Management Appsmentioning
confidence: 99%
“…We also conducted a series of accessibility studies [ 18 , 19 ] to inform development for individuals with motor, cognitive and sensory impairments. We then conducted a clinical trial of the system in a group of adults with SB and found that higher utilization of the mHealth system resulted in improved self-management outcomes [ 20 ]. Additionally, a personal health record module and a module that educates users on issues relevant to their health have been subsequently built.…”
Section: Introductionmentioning
confidence: 99%